The detoxification and utilization of cyanide tailings: A critical review. (15th June 2021) - Dong, Kaiwei; Xie, Feng; Wang, Wei; Chang, Yongfeng; Lu, Diankun; Gu, Xiaowei; Chen, Chunlin
Abstract: Cyanide tailings are industrial hazardous solid wastes arising from gold mining industry. Hundreds of millions of tons of cyanide tailings that contain highly toxic cyanides and various valuable elements, such as gold, silver, iron, sulfur, copper, lead, and zinc are generated and discharged to tailing dams every year. Significant efforts have been undertaken to develop efficient detoxification and utilization technologies to reduce hazardous wastes and recover the valuable element in cyanide tailings. In this paper, the sources and characteristics of cyanide tailings are introduced. The technologies using various physical, chemical, and biological methods or a combination thereof to detoxify and utilize cyanide tailings are reviewed. However, the complexity of cyanide tailings and the high cost of treatment may seriously restrict their industrial application. It seems that thermal treatment with catalysts and autoclaved hydrolysis are certainly promising technologies for the detoxification of cyanide tailings with the removal rate of cyanides more than 99%, which can be good for the cleaner production of gold mining. The current research status and the obstacles in the recovery of cyanide, gold-silver, sulfur-iron, copper-lead-zinc, and "low-value content" from cyanide tailings are then reviewed in detail. These processes can be used independently or in conjunction with other treatment methods depending on the nature of cyanide tailings. The detoxification and comprehensive utilization of cyanide tailings would ultimately bring economic and environmental benefits. Highlights: Sources and characteristics of cyanide tailings are identified. Methods for detoxification of cyanide tailings are reviewed in terms of physical, chemical, and biological. Various technologies for utilization of cyanide tailings are concluded based the composition.